2020
DOI: 10.1111/1750-3841.15102
|View full text |Cite
|
Sign up to set email alerts
|

DMHF (2,5‐dimethyl‐4‐hydroxy‐3(2H)‐furanone), a volatile food component generated by the Maillard reaction, promotes appetite and changes gene expression in the rat brain through inhalation

Abstract: Inhalation of odors can affect physiological parameter and change gene expression-related specific function. 2,5-Dimethyl-4-hydroxy-3(2H)-furanone (DMHF) is one of the major odor compounds generated by the Maillard reaction. We previously reported that the inhalation of DMHF decreased systolic blood pressure via the autonomic nervous system in rats. The autonomic nervous system is also closely related to appetite regulation. The present study investigated the effects of DMHF on dietary intake and gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Also, DMHF with high FD factor and OAV would be a key responsible agent for the physiological activities. We previously found that the inhalation of DMHF at 5.7 ppm to Wistar rats decreased SBP 32 and promoted appetite 45 via parasympathetic nerve activity. As shown in Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Also, DMHF with high FD factor and OAV would be a key responsible agent for the physiological activities. We previously found that the inhalation of DMHF at 5.7 ppm to Wistar rats decreased SBP 32 and promoted appetite 45 via parasympathetic nerve activity. As shown in Fig.…”
Section: Discussionmentioning
confidence: 95%
“…DMHF also stimulates feeding behavior via the autonomic nervous system 45 . The oral ingestion is a factor for the change of physiological outcomes and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mRNA expression related to appetite and neurotransmission in the rat brain was also altered. These studies indicated that HDMF affected appetite both through gene expression at the mRNA level and autonomic nervous system . In addition, HDMF inhalation was found to affect generation of brainwaves, and a lower concentration (under 40 mg/L) may induce relaxation effects in the brain while a higher concentration (above 40 mg/L) may have opposite effects .…”
Section: Sensory Significancementioning
confidence: 99%
“…These studies indicated that HDMF affected appetite both through gene expression at the mRNA level and autonomic nervous system. 63 In addition, HDMF inhalation was found to affect generation of brainwaves, and a lower concentration (under 40 mg/L) may induce relaxation effects in the brain while a higher concentration (above 40 mg/L) may have opposite effects. 64 In the glycine/glucose Maillard reaction, HDMF was considered a main contributor for mood changes and sedative effects on the central and autonomic nervous system since it was one of the strongest potent odorants in terms of aroma extraction dilution analysis (AEDA).…”
Section: ■ Sensory Significancementioning
confidence: 99%